Tephrochronology of core PRAD 1-2 from the Adriatic Sea: insights into Italian explosive volcanism for the period 200–80 ka. (15th May 2015) - Bourne, A.J.; Albert, P.G.; Matthews, I.P.; Trincardi, F.; Wulf, S.; Asioli, A.; Blockley, S.P.E.; Keller, J.; Lowe, J.J.
Abstract: Core PRAD 1-2, located on the western flank of the Mid-Adriatic Deep, was investigated for tephra content within the part of the sequence assigned on biostratigraphic and sapropel-layer stratigraphy to MIS 5 and 6 (ca. 80–200 ka BP). A total of 11 discrete tephra layers are identified, 8 visible and 3 cryptotephra layers. 235 geochemical measurements obtained from individual glass shards using WDS-EPMA enabled 8 of the 11 tephras to be correlated to known eruption events, 5 of which are represented in the Lago Grande di Monticchio (LGdM) regional tephra archive sequence. Three of these layers are recognised ultra-distally for the first time, extending their known distributions approximately 210 km further north. The results provide an independent basis for establishing an age-depth profile for the MIS 5–6 interval in the PRAD 1-2 marine record. This approach allowed age estimates to be interpolated for the tephra layers that could not be correlated to known events. It also provides an independent test of, and support for, the broad synchroneity of sapropel-equivalent (S-E) events in the Adriatic Sea with the better-developed sapropel layers of the eastern Mediterranean, proposed by Piva et al. (2008a). Highlights: Eleven tephra layers are identified in PRAD 1-2 between MIS 5 and 6. Five layers can be correlated to tephras present in Lago Grande di Monticchio. Three layers are correlated to Mediterranean marker layers, X-6, W-1 and V-2. Extends known distributions of the layers 210 km to the north. Tephra data suggests there may be a case for re-examination of the sapropel 6 age.